A combined approach to identify isolated theropod teeth from the Cenomanian Kem Kem Group of Morocco: cladistic, discriminant, and machine learning analyses - Hendrickx, Christophe; Trapman, Thomas H.; Wills, Simon; Holwerda, Femke M.; Stein, Koen H.W.; Rauhut, Oliver W.M.; Melzer, Roland R.; Woensel, Jeroen V.A.N.; Reumer, Jelle W.F. (Journal of Vertebrate Paleontology, 2023)
The Kem Kem Group of Southeastern Morocco, North Africa, is well known for theropod remains, especially isolated teeth. Here, a collection of isolated theropod teeth is assessed for diversity using a combination of linear discriminant, phylogenetic, and machine learning analyses for the first time. The results confirm earlier studies on Kem Kem theropod diversity, with teeth referred to Abelisauridae, Spinosaurinae, and Carcharodontosauridae. A single tooth is ascribed to a non-abelisauroid ceratosaur or a megaraptoran and may represent the enigmatic averostran Deltadromeus. Spinosaurine teeth are clearly differentiated by all three methodologies, whereas abelisaurid and carcharodontosaurid teeth could only be distinguished by the machine learning and phylogenetic analyses. This study shows that a combination of independent methods is most effective at providing strong evidence on theropod dental diversity in a particular assemblage, and that cladistic and machine learning analyses are the most reliable approaches to identify isolated dinosaur teeth. The methodology used here is likely to yield results in other dinosaur assemblages where isolated teeth are more abundant than body fossils.
CRIS-Team Scopus Importer:2024-12-16